White matter microstructure and connectivity changes after surgery in male adults with obstructive sleep apnea: recovery or reorganization? - Chai, Yaqiong; Park, Hea Ree; Jo, Hyunjin; Seo, Min Young; Kim, Hyo Yeol; Joo, Eun Yeon; Kim, Hosung (Frontiers in Neuroscience, 2023)
Study Objectives: Obstructive sleep apnea (OSA) is a prevalent clinical problem significantly affecting cognitive functions. Surgical treatment is recommended for those unable to use continuous positive airway pressure. We aimed to investigate the therapeutic effect of upper airway surgery on white matter (WM) microstructure and brain connectivity in patients with OSA. Methods: Twenty-one male patients with moderate to severe OSA were recruited for multi-level upper airway surgery. Overnight polysomnography (PSG), neuropsychiatric tests, and brain MRI scans were acquired before and 6.1±0.8 months after surgery. Nineteen male patients with untreated OSA were also included as a reference group. We calculated the longitudinal changes of diffusion tensor imaging (DTI) parameters, including fractional anisotropy (△FA) and mean/axial/radial diffusivity (△MD/AD/RD). We also assessed changes in network properties based on graph theory. Results: Surgically treated patients showed improvement in PSG parameters and verbal memory after surgery. Globally △FA was significantly higher, and △RD was lower in the surgery group compared to the untreated group. Especially △FA of the tracts involved in the limbic system was higher after surgery. In network analysis, higher △betweenness and lower △clustering coefficients were observed in the surgical group compared to the untreated group. Finally, the improvement of verbal memory after surgery positively correlated with △FA in superior thalamic radiation (p=0.021), frontoaslant tracts (p=0.027), and forceps minor tracts (p=0.032). Conclusion: Surgical treatment of OSA can alleviate alterations in WM integrity and disruptions in local networks, particularly for the tracts involved in the limbic system. These findings may further explain the cognitive improvement observed after the treatment of OSA.